An Analysis Of 3 Phase Ac Motor As A Water Pump Drive In PDAM Tirtanadi Booster Pump - Syahrijal Umri; Amani Darma Tarigan; Solly Aryza (Sean Institute, 2024)
Energy efficiency, even though it is small, will have a big impact in terms of power, economy, environment, and others. Many potential energy savings can be explored, one of which is from motor performance. The 3-phase AC motor is the main electricity user in a modern industry. The average electricity consumption for electric motors ranges from 65-70% of the total electricity cost. This study aims to determine the efficiency value of the 3-phase AC motor as a pump driver. The research method used is by means of literature study, measurement, and data processing. The methodology in data collection is carried out with the criteria for sampling the motor, measurement, and output analysis. From the results of the analysis, it is known that the average 3-phase AC motor for the work of Centrifugal pumps on the Booster Pump Tower Water PDAM Tirtanadi work at an efficiency of 47.42% of the load. This result can be called a reduction in improvement considering that maximum efficiency occurs in the range of 75-80%. The amount of energy wasted if realized will have many negative impacts that are detrimental to the company, one of which is productivity